Interfaces e transformações de práticas e conhecimentos na agricultura: um ensaio bibliográfico sobre a emergência das novidades - Medeiros, Monique; Marques, Flávia Charão (Universidade Federal Rural do Rio de Janeiro, 2015)
The history of agriculture is marked by 'novelty production', in which farmers creatively combine knowledge and factors of production. The homogenization technique intended for the modernization of agriculture and represented by the guidelines of the so-called ‘Green Revolution’, has been associated with negative consequences in social-environmental terms in rural areas. However, recent proposals that aim to set new dynamic processes of development, have been constructed in opposition to conventional diffusionist ideas. With this, proposals and projects that emphasize the need for development of local knowledge have been advancing. In this context, it is considered that changes and innovations are constantly occurring and could be very motivating for an active process of "Novelty Production”, in which the location and action of multiple actors are fundamental. Grounded in these ideas and in the light of a recent theoretical discussion, this paper brings a reflection by different authors on the theoretical dimension of the debate on the effect of transforming practices and generating knowledge related to them.